If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.50(10x + -2) = 4 Reorder the terms: 0.50(-2 + 10x) = 4 (-2 * 0.50 + 10x * 0.50) = 4 (-1 + 5x) = 4 Solving -1 + 5x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 4 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 4 + 1 5x = 4 + 1 Combine like terms: 4 + 1 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 | | 146-3x=33x+18 | | 11-9x=175-37x | | 0.0625x^2-0.125x=1 | | x^2-2x+1=8 | | 18x-(2x-8)=40 | | 37-3x=6x+27 | | 68-4x=8x-20 | | 7-8x=127-29x | | -10=-5(t-8) | | 7-8x=127-39x | | z^2-15=0 | | 3(x+7m+5)= | | 3x-12=4x-12 | | 50(x)=-0.4x^2+80x-1600 | | -21=7y | | 5(x+2)-7(x-1)=1 | | c+5=3 | | (8z-2)(8-z)=0 | | x(7x+32)+33=0 | | 2m=m+6 | | 5x^2+6x=31 | | -x-5=6 | | (n-4)*3=15 | | 20-c=12 | | 3(x+3)-2(x-1)=17 | | 7(x+2)=21 | | 11x-5=73 | | 2(x-5)+3(x-1)=32 |